Simple Arrangement of Children’s Song with Trilingual Characters As Learning Media For PGSD and PGMI Students - Sinaga, Syahrul Syah; Widayanti, Maria Johana Ari; Andaryani, Eka Titi; Muchsin, Ibnu Amar (Universitas Negeri Semarang, 2023)
The existing quality of learning media, particularly in teaching multilingual characters of Early Childhood Education, poses a challenge in education. Teachers should possess the skills to continuously innovate in creating instructional materials, including prospective teachers, namely PGSD and PGMI students. This program aims to enhance the skills of PGSD and PGMI students in developing multilingual character education media for children. The primary focus is on using children's songs as an engaging and effective educational tool. Another issue is the need for more skills among students in creating multilingual and character-based instructional media that can captivate children's interest. The ultimate goal is to improve students' skills in creating engaging and effective instructional media, providing benefits to children, and contributing positive knowledge to the general public. As a solution, this program creates a simple arrangement of children's songs with characters in three languages as instructional media for PGSD and PGMI students. In its implementation, students are equipped with the skills to create simple arrangements of children's songs with the hope that this will serve as valuable preparation for creating engaging instructional materials.